Manajemen Pembinaan Karakter Santri Di Pesantren Salafiyah Perspektif Pendidikan Islam (Studi Pondok Pesantren Raudatul Ulum 1 Kabupaten Malang) - Widodo, Wahyudi (Wibawa : Jurnal Manajemen Pendidikan, 2025)
Character is one of the things that needs to be in a person, including students. This is because having a strong character will have a good impact on future life and can face all the challenges of the times. Therefore, pesantren management is very important related to student development. The research method used is qualitative with interview and observation data sources. The results of the study show that 1) In the management of character development, there are three important things that exist, namely careful planning, orderly and purposeful implementation, and sustainable evaluation. In planning, the two most important things besides VISION MISSION are the source of funds and the curriculum. At PP Raudhatul Ulum 1 Malang, there are three sources of funds for Islamic boarding schools and their activities, namely: the business of the Islamic boarding school, the tuition of students, and assistance from the community in general. The curriculum used in the pesantren is the salaf pesantren curriculum, but it still integrates with the national curriculum and modernization of the current era. 2) Forms of character development of students are seen from the activities of the pesantren. Where pesantren has three activities, namely recitation activities on books, activities to the community related to worship that are widely practiced in the community such as prayers, and extracurricular activities that support the development of the character and abilities of students, both religious science, art, sports and technology. As a result, many students who when they graduate get college scholarships and are immediately accepted into the workplace or create jobs.